Extending the Technology Acceptance Model in the Impact of Vocational Educators’ Gender, Experience and Perception - Ifeanyi Edeh, Nathaniel; Ugwoke, Ernest O; Abanyam, Friday Ekahe; Anayo Madu, Maureen; Odums Augustine, Narborth; Chukwuma Pulife, Matthew (Journal of Technical Education and Training, 2021)
The study considered extending the technology acceptance model in learning-management-systems in TVET: The impact of vocational educators’ gender, experience and perception. A mixed research design was adopted for this study with 1314 TVET educators as the population. A sample of 386 respondents comprising of 234 and 152 vocational educators from federal and state institutions were selected based on Taro Yamene’s formula afterwards, proportionate sampling technique was used to determine the number of the vocational educators for each institution. The instrument for data collection was a structured questionnaire titled: “TVET Educators Experience and Perception of LMS Questionnaire” (TEEPLMSQ). The reliability of the instrument was determined using Cronbach’s Alpha which yielded reliability indices of (? = .761); (? = .816), (? = .832) with a high grand coefficient of 0.80 for vocational educators’ perception, LMS skills possessed and barriers militating against LMS use respectively. Data collected were analyzed using bivariate correlation, regression, and also path analysis through 5000 re-samples bias-corrected (BC) bootstrapping method, as well as confirmatory factor analysis. The result of the study revealed that vocational educators in Enugu and Anambra States of Nigeria perceived LMS as a credible ICT tool that supports the teaching of TVET courses and enhances the transfer of TVET skills to TVET students. The path analytical results revealed that lecturers’ characteristic (experience) has full mediation effects between the LMS skills possessed and level of LMS usage. Based on the findings of the study, it was recommended among others that The TVET educators should adopt LMS in teaching and learning of TVET courses in Nigerian tertiary institutions.